Beyond the Early Adopters: Escape Rooms in Science Education - Veldkamp, Alice; Knippels, Marie-Christine P. J.; van Joolingen, Wouter R. (Frontiers in Education, 2021)
Case studies report enthusiastically on the implementation of escape rooms in science education. This mixed-method study explores beyond the early adopting teacher, as the perceptions of 50 teachers and 270 students were investigated. Escape rooms are time restricted games where participants work together and accomplish a specific goal. The escape rooms’ usability for education in terms of goals, experiences during gameplay, outcomes, and boundary conditions are studied, using multiple data sources: online questionnaires, interviews, classroom observations and movie clips made by students about their experiences. The use of mixed methods and large samples on this topic is a novelty. Results show that teachers of different ages, gender and teaching experience were appealed in particular to the diversity of activities offered that call for multiple skills and teamwork. Students experienced the need to think hard using multiple thinking skills and enjoyed the feeling of autonomy and mastery during gameplay. This is interesting, as an escape room setup is very strict, with few degrees of freedom. According to teachers and students, escape rooms are suitable for processing, rehearsing and formative assessment of science knowledge and skills. However, the time restriction during gameplay appears to be an ambiguous factor in student learning.